Compositional analysis of invertebrate communities in Raja Ampat conservation zones using environmental DNA (eDNA) - Ruzanna, Arina; Madduppa, Hawis; Butet, Nurlisa Alias (Journal of Marine Studies, 2024)
Raja Ampat conservation area is divided into three zones: the core zone, the tourism zone, and the open zone. This region is crucial for sustainable fisheries and environmental management, yet it is under significant anthropogenic pressure. Accurate species detection is essential for inventory and diversity surveys, and environmental DNA (eDNA) methods have been shown to be more effective than conventional techniques. This study aimed to evaluate whether V9 primers could detect multispecies invertebrate compositions, assess community structure and contributions within each zone, and identify significant differences in invertebrate diversity among the zones. A total of 66 eDNA samples were collected from water and sediment columns across the three zones. Samples were extracted using the NucleoSpin„¢ kit (Macherey-Nagel) protocol, amplified with universal eukaryote primers targeting the 18S gene, and sequenced using Illumina MiSeq. Taxonomic analysis was performed using QIIME2 software and the SILVA database. The study identified 19 invertebrate species. The Shannon-Wiener (H') and Simpson (D) indices revealed greater species diversity in the core zone compared to the tourism and open zones. However, the Kruskal-Wallis test indicated no significant differences in species diversity across the zones. SIMPER analysis demonstrated a high percent contribution of species in each zone. This study highlights the effectiveness of eDNA methods for biodiversity assessment and offers valuable insights into invertebrate community structures within the Raja Ampat conservation area.